Awareness of HPV infection and attitudes toward HPV vaccination among Latvian adolescents. Issue 2 (26th February 2017) - Patel, Hersha; Pčolkina, Kristine; Strazdina, Kristine; Viberga, Ilza; Sherman, Susan M.; Tincello, Douglas G.; Redman, Charles W.; Rezeberga, Dace; Moss, Esther L.
Abstract: Objective: To evaluate awareness of HPV and its vaccine among Latvian adolescents. Methods: A cross‐sectional survey was conducted in a 2‐week period in September 2015 among 270 adolescents attending a secondary school in Riga, Latvia. All students present during sexual‐health classes (grades 10–12 [aged 16–21 years]) were included. A self‐administered paper‐based survey assessed sociodemographic factors, sexual behaviours, smear history and knowledge of sexually transmitted infections, HPV and HPV vaccine knowledge, and sources of information. Results: Overall, 121 surveys were completed (62 by male students and 59 by female students). Latvian adolescents lacked awareness of HPV: only 26 (21.5%) had heard of HPV (21 [35.6%] female students vs 5 [8.1%] male students; P< 0.001) and 12 (9.9%) of the HPV vaccine. Eighty (66.1%) participants felt inadequately informed about HPV. However, the adolescents partook in high‐risk behaviours: 70 (57.9%) students were sexually active, 26 (37.1%) of whom had already had three or more sexual partners. Conclusion: Despite the high prevalence of HPV in Latvia, poor knowledge about HPV infection among adolescents could explain low uptake of the HPV vaccine by this high‐risk population. Therefore, educational strategies that highlight the consequences of HPV could promote acceptance of vaccination. Abstract : Awareness of HPV infection and its consequences among Latvian adolescents was poor, which might explain the low levels of HPV vaccine uptake in this population.